Penerapan Algoritma Sequitur Pada Kompresi Record Database Pada Database - Sarbudi Siahaan (JURIKOM (Jurnal Riset Komputer), 2019)
The rapid development of information technology has become a very important role for rapid information exchange. One solution to the problem above is by compressing data both in the form of text, voice and image data before it is transmitted and then the recipient will reconstruct it back into the original data (decompression). Compression or compression is one of the sciences in the computer field. Compression is done because of limitations in memory space, limitations of data storage media, and the need for limited data transfer time. In the rapid development of technology, a data storage media has become an obligation that must be owned by every human being who is always associated with computers, both internal data storage and external data storage. Just as a database (database) has become a basic requirement for every individual or organization to run a computerized activity. Database (database) is a collection of text data that forms a file that is interconnected with certain procedures to form new data or new information. However, a database is said to be good if there is no data redundancy, good access speed and file size in memory is not large. Data compression in database records is very helpful in overcoming data redundancy, speeding up data access and reducing the size of a file. Compression of database records in the database aims to reduce the number of duplicate (equal) entries that will be stored in a database. This will certainly reduce the number of input characters that will be stored and will automatically reduce the size of files in the computer's memory space